Immunogenicity of protein aggregates of a monoclonal antibody generated by forced shaking stress with siliconized and nonsiliconized syringes in BALB/c mice. (21st June 2017) - Uchino, Tomonobu; Miyazaki, Yasunori; Yamazaki, Takuto; Kagawa, Yoshiyuki
Abstract: Objective: In this study, we aimed to investigate the immunogenicity of protein aggregates of monoclonal antibodies (mAbs), generated by forced shaking stress with siliconized and nonsiliconized syringes in a mouse model. Methods: Samples were filled in siliconized and nonsiliconized syringes with shaking and headspace air. Characterization studies were performed using high-performance size-exclusion chromatography, nanoparticle tracking analysis, flow cytometry, micro-flow imaging and resonant mass measurement. The samples (10 or 100 μg) were subcutaneously injected into BALB/c mice for 21 days, and the anti-drug antibody (ADA) concentrations were monitored. Key findings: In samples shaken with siliconized syringes [SO (+)], large amounts of submicron and subvisible protein aggregates were formed by interactions with silicone oil droplets. The characteristics of protein aggregates differed between the mAb solution and shaken samples, which strongly indicates that silicone oil accelerates protein aggregation. When administered at low doses, the ADA concentration in all samples increased with repeated injections, and SO (+) induced the highest immunogenicity. However, when administered at high doses, ADA concentration decreased following prolonged repeated administration for tolerance. Conclusions: These results indicated that mAb protein aggregation induced immunogenicity in mice, and SO (+) induced higher immunogenicity than samples shaken with nonsiliconized syringe.